The Suitability of Recycled Domestic Wastewater in Plain Concrete Production. - Orishaba, James (Kabale University, 2023)
Concrete production is one of the activities that use a lot of water in its mix but fresh potable water is greatly reducing due to highly increasing population and industries in the world. Therefore, there is need for identifying alternative sources of water which one of them is recycling wastewater to be used for concrete production. This project therefore sought to evaluate the suitability of recycled domestic wastewater in concrete production for use.